Kemampuan Unit Usaha Yayasan Nurul Hayat Dalam Menunjang Biaya Operasioanal Lembaga Amil Zakat - Novalia Nastiti; Imron Mawardi (Universitas Airlangga, 2014)
Amil zaka in zaka institutions has the right as one of eight ashnaf. Their rights are usually used by zaka institutions as operational cost. However, not all of the intitutions which manage zaka take amil’s right, one of them is Yayasan Nurul Hayat. This institution does not take amil’s right and it is independent in its operational cost. To support this operational cost, Yayasan Nurul Hayat establish business unit with utilize its profit.This study aimed to discover the capability of business unit in supporting operational cost of Yayasan Nurul Hayat. This study used a qualitative approach with descriptive case study method. The selections of informant are using purposive sampling method. Data collection was conducted by semi-structured interviews and documentation. This data is analyzed using descriptive method.The result of this study shows that Yayasan Nurul Hayat Employments’ Salary is taken from business unit’s profit. It is also used to give bonus for employments and grow the business unit of Yayasan Nurul Hayat up. From the result of this study, it can be concluded that the business unit which is developed has great capability to support operational cost of Yayasan Nurul Hayat. REFERENCESAr-Rifa'i, Muhammad. Nisab. (1999). Ringkasan Tafsir Ibnu Katsir. Jakarta: Gema Isnasi Press.Ash Shiddieqy, Teungku. Muhammad Hasbi. (2005). Pedoman Zakat. Semarang: Hayam Wuruk.Fakhruddin. (2008). Fikih dan Manajemen Zakat di Indonesia. Malang: UIN Malang Press.Hafidhuddin, Didin. (2002). Zakat Dan Peningkatan Kesejahteraan (Upaya Memahami Kembali Makna dan Hakikat Zakat) dalam Mimbar Agama dan Budaya. Jakarta: UIN Syarif Hidayatullah.Hafidhuddin, Didin. (2003). Panduan Zakat bersama Dr. KH. Didin Hafidhuddin. Jakarta: Republika.Hikmat, & Hidayat. (2008). Panduan Pintar Zakat. Jakarta: Qultummedia.Ja'far, Muhammadiyah (1985). Zakat Puasa dan Haji. Jakarta: Kalam Mulia.Ja'far, Muhamaddiyah. (2003). Tuntunan Ibadah Zakat, Puasa dan Haji. Jakarta: Kalam Mulia.Nafarin, M. 2004. Penganggaran Perusahaaan, Edisi Revisi, Salemba Empat, Jakarta.Purwanto, April. (2009). Manajemen Fundraising bagi Organisasi Pengelola Zakat. Yogyakarta: Sukses.Qardawi, Yusuf. (1984). Atsar al-Zakat lil afrad wa al-mujtamaat. Seminar Zakat I.Qardawi, Yusuf. (2004). Hukum Zakat: Studi Komparatif Mengenai Status dan Filsafat Zakat Berdasarkan AlQur’an dan Al-Hadits, terj. Salman Harun, et al. Bogor: PT. Pustaka Litera AntarNusa.Rais, M. Amien. (1994). Cakrawala Islam antara Cita dan Fakta. Bandung: Mizan.Rifa'i, Hasan. (1996). Panduan Zakat Praktis, cet.1. Jakarta: Dompet Dhuafa Republika.Rofiq, Ahmad. (2004). Fiqh Kontekstual: dari Normatif ke Pemaknaan Sosial. Yogyakarta: Pustaka Pelajar.Shabir, Muslich. (2005). Pemikiran Syekh Muhammad Arsyad Al-Banjari tentang Zakat: Suntingan Teks dan Analisis Intelektual. Jakarta: Nuansa Aulia.Shihab, M. Quraish. (1992). Membumikan Al-Qur’an: Fungsi dan Peran Wahyu dalam Kehidupan Masyarakat. Bandung: Mizan.Sudarsono, Heri. (2008). Bank dan Lembaga Keuangan Syariah Deskripsi dan Ilustrasi. Yogyakarta: Ekonesia.